Functional crosstalk between non‐canonical caspase‐11 and canonical NLRP3 inflammasomes during infection‐mediated inflammation - Yi, Young‐Su (Immunology, 2019)
Inflammation is a part of the body's immune response for protection against pathogenic infections and other cellular damages; however, chronic inflammation is a major cause of various diseases. One key step in the inflammatory response is the activation of inflammasomes, intracellular protein complexes comprising pattern recognition receptors and other inflammatory molecules. The role of the NLRP3 inflammasome in inflammatory responses has been extensively investigated; however, the caspase‐11 inflammasome has been recently identified and has been classified as a ‘non‐canonical’ inflammasome, and emerging studies have highlighted its role in inflammatory responses. Because the ligands and the mechanisms for the activation of these two inflammasomes are different, studies to date have separately described their roles, although recent studies have reported the functional cooperation between these two inflammasomes during an inflammatory response. This review discusses the studies investigating the functional crosstalk between non‐canonical caspase‐11 and canonical NLRP3 inflammasomes in the context of inflammatory responses; moreover, it provides insight for the development of novel anti‐inflammatory therapeutics to prevent and treat infectious and inflammatory diseases.